Effectiveness of Elementary School Management through Digital Literacy, Infrastructure Readiness, Hybrid-Based Organizational Culture (Integration of Artificial Intelligence and Data-Driven Decision Making): An Empirical Study - Lia Nurhayati (Newinera Publisher, 2026)
This paper explored the effectiveness of elementary school management based on a hybrid model that means fusing data driven decision making with artificial intelligence in government elementary schools in the Gorontalo Regency of Indonesia. The study utilized a quantitative explanatory research design to explore the impact of digital literacy, infrastructure preparedness, and organization culture on the effectiveness of school management. The sample size consisted of principals, teachers, and administrative personnel and 205 respondents were chosen by proportional stratified random sampling. A Likert scale questionnaire was used to gather data and Structural Equation Modeling with Partial Least Squares was used to analyze the data. The results found that digital literacy, infrastructure preparedness, and organizational culture had a positive impact on management effectiveness. The strongest predictor was found to be digital literacy and then organizational culture and infrastructure readiness became the predictors. These three predictors had a high explanatory power, and the value of R square was 0.714, which showed that three predictors explained 71.4 percent of the variance in the effectiveness of management in schools. These findings imply that effective deployment of hybrid data based and AI supported school management does not merely require the presence of technology but also the ability of school actors to comprehend data, cooperate and maintain adaptable organizational behavior. This research concludes that the promotion of effective and context sensitive digital transformation in the management of elementary schools must be made priorities by enhancing digital literacy and cultivating a positive organizational culture.